"WE ARE ALL IN THE SAME BOAT NOW" PROVERBIAL RHETORIC IN THE CHURCHILL-ROOSEVELT CORRESPONDENCE - Mieder, Wolfgang (International Journal of English Studies, 2009)
Both Winston S. Churchill (1874-1965) and Franklin D. Roosevelt (1 882-1945) were masters of the English language and effective orators, rallying their people through word and deed to fight as allies against the dictatorial powers during the Second World War. Their public speeches and interviews are replete with proverbs, proverbial expressions, and other phraseologisms. This is also true for their private and secretive letters, messages, memoranda, and telegrams, as can be seen from the materials that Warren F. Kimball edited in the three volumes of Churchill & Roosevelt: The Complete Correspondence (Princeton, NJ: Princeton University Press, 1984). The proverbial language, especially metaphorical texts referring to the body, animals, and the military, gives their important communications a lively and humane flavor that illustrates their deep friendship, trust, and support of each other. Frequently used as metaphorical arguments, these proverbial interjections into an otherwise factual epistolary exchange from 1933 to 1945 bear witness to the determination of these two world leaders to win the struggle for a free world.